UMANG AN EMERGENCY CAMPAIGN TO ADDRESS MALNUTRITION - Gnanaraj, Grana Pu Selvi (Indian Journal of Community Health, 2015)
Background: World Vision India with its existence in across the country implemented the emergency feeding program for the children with underweight in 53 area development sites spread across 15 states of the country. Rationale: Since more than 40% of the children were found to be underweight through our assessment process, we implemented this community based feeding program as an emergency response to children with malnutrition. Objective: To rehabilitate the malnourished children and sensitise the community on feeding, caring and health seeking practices. Material and Methods: Considering the high prevalence of underweight children, we initiated the program ‘UMANG’ (Urgent Management and Action for Nutritional growth) on a campaign mode with the involvement of various stakeholders. Malnourished children for this program were selected through a community based screening program. This was a 90 day community based feeding program for the malnourished children conducted either in the anganwadi center or a common place. Underweight children (moderate and severe) and their mothers/care takers attended this program with their contribution from backyard nutrition garden or local market and were taught to prepare a nutritious menu using locally available low cost food materials. Mothers were also sensitised on health seeking, caring and feeding practices to prevent future incidence of malnutrition. The families of the malnourished children were also supported with nutrition (backyard) garden, economic development assistance to improve food diversity at the household level. Results: About 50858 malnourished children (54 per cent moderate and 46 per cent severe) were enrolled in UMANG[1]. On comparing the baseline (1st day) and endline figures (90th day) 38.5 per cent of the children have graduated to normal from moderate and severe underweight. In addition UMANG had spin off benefits such as increase in anganwadi attendance, community based growth monitoring in place, communities with increase in the knowledge on malnutrition and formation of common interest groups to prevent malnutrition. Conclusion: UMANG is a comprehensive program which improves the nutritional status of the children and has the potential to prevent future incidences of malnutrition.